Pola Asuh Dan Pendapatan Keluarga Dengan Kejadian Stunting Pada Anak Usia 2-5 Tahun Di Wilayah Kerja Puskesmas Bohabak - Mirna Kawulusan; Rivolta G.M. Walalangi; Jufri Sineke; Regita C. Mokodompit (Jurnal GIZIDO, 2019)
Stunting is defined as height according to age -2 standard median child growth curve. One of the causes of stunting is poor parenting practices. Family income influences a person's ability to access certain foods which affect the nutritional status of children. The purpose of this study was to determine the pattern of fostering and family income with stunting in the work area of ​​the Bohabak Health Center, North Bolaang Mongondow Regency. his type of research is analytic observational using cross sectional design. The number of samples determined by Purposive Sampling as many as 41 people aged 2-5 years. Bivariate data analysis used Chi square test with Fisher's Exact value. The results showed the sample in the short category is 68.3% and in the very short category 31.7%, the sample gets good parenting ie 63.4% and parenting less 36.6%, the sample that has high family income is 22% and low family income 78%. It is known that there is no significant relationship between Parenting and Stunting in children aged 2-5 years in the work area of ​​the Bohabak Health Center. There is a significant relationship between family income with the incidence of stunting in children aged 2-5 years in the work area of ​​the Bohabak Community Health Center. It is recommended for puskesmas especially nutrition programs to provide counseling to adolescents, women of childbearing age and pregnant women about the causes of stunting and the importance of handling the First 1000 Days of Life.